2016
DOI: 10.1038/ng.3708
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genomic loci associated with resting heart rate and shared genetic predictors with all-cause mortality

Abstract: Resting heart rate is a heritable trait correlated with life span. Little is known about the genetic contribution to resting heart rate and its relationship with mortality. We performed a genome-wide association discovery and replication analysis starting with 19.9 million genetic variants and studying up to 265,046 individuals to identify 64 loci associated with resting heart rate (P < 5 × 10); 46 of these were novel. We then used the genetic variants identified to study the association between resting heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
135
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(156 citation statements)
references
References 39 publications
7
135
3
Order By: Relevance
“…Elevated RHR may also reflect underlying arrhythmias, which increase mortality risk 32. Although RHR has been thought to be a silent bystander,33 a recent genome-wide association study has confirmed the causal role of genetically determined RHR in mortality,34 which found relative risks larger than those of our study. Few data exist exploring the association between RHR and the risk of cancer.…”
Section: Discussioncontrasting
confidence: 47%
“…Elevated RHR may also reflect underlying arrhythmias, which increase mortality risk 32. Although RHR has been thought to be a silent bystander,33 a recent genome-wide association study has confirmed the causal role of genetically determined RHR in mortality,34 which found relative risks larger than those of our study. Few data exist exploring the association between RHR and the risk of cancer.…”
Section: Discussioncontrasting
confidence: 47%
“…In a large GWAS, combining 46 loci associated with RHR, only 2.5% of the variance of RHR was explained 1. Here, a genetically predicted RHR increase of 5 bpm increased the risk of mortality by 20%.…”
Section: Discussionmentioning
confidence: 79%
“…Genome-wide association studies (GWAS) have so far found several genetic loci that are significantly associated with RHR. However, when combining the GWAS identified heart rate-increasing alleles, only a few percentages of the variance in heart rate is explained 1. Using the classical twin design, the relative contribution of genetic and environmental factors can be determined.…”
Section: Introductionmentioning
confidence: 99%
“…This finding, that mortality selection may lead to attenuation, has also been observed in the context of Mendelian randomization. 5,6 If certain genetic profiles are associated with increased risks for mortality, 38,39 then individuals with such genotypes are less likely to be observed in older samples (e.g. Figure 4).…”
Section: Discussionmentioning
confidence: 99%